Evaluation of Biochemical Changes in Skin-Derived Mesenchymal Stem Cells during In Vitro Neurodifferentiation by FT-IR Analysis. Issue 5 (11th July 2012) - Parfejevs Parfejevs, V. V.; Gavare Gavare, M. M.; Cappiello Cappiello, L. L.; Grube Grube, M. M.; Muceniece Muceniece, R. R.; Riekstina Riekstina, U. U.
Abstract : Recently FT-IR analysis has been employed to study changes in molecular signatures during embryonic stem cell differentiation. We were interested to find out whether FT-IR spectroscopy could be applied to analyze changes in human skin mesenchymal stem cell (S-MSC) biochemical profile during in vitro neurodifferentiation. S-MSCs were propagated in serum-free medium with EGF and FGF-2 during six weeks. Neural progenitor cell line ReNcell CX (Millipore) was used as a reference cell line. Samples were collected each week and analyzed for neural marker nestin, tubulin β III, GFAP, and CD271 expression. FT-IR analysis was carried out using microplate reader HTS-XT (Bruker, Germany). Despite the immunophenotype similarity, FT-IR spectroscopy revealed distinct profiles for S-MSC culture and ReNcell CX cells. FT-IR spectra analyses showed changes of protein and lipid concentration during neurodifferentiation and different carbohydrate composition in ReNcell CX and S-MSCs. It was possible to discriminate between S-MSC cultures at different time points during neurodifferentiation. The results of this study demonstrate that FT-IR spectroscopy is more sensitive than conventional immunophenotyping analysis and it has a great potential for the monitoring of the stem cell differentiation status.